2022
DOI: 10.31671/doujournal.1035962
|View full text |Cite
|
Sign up to set email alerts
|

Sürdürülebi̇li̇r Kalkinma Bağlaminda Uluslararasi Üni̇versi̇te Siralama İndeksleri̇ Ve Türki̇ye’deki̇ Üni̇versi̇teler

Abstract: Pınar GEDİKKAYA (BAL) (1) , Melek Özlem AYAS (2) , Tuba BOZAYKUT (3) , Burcu YAVUZ TİFTİKÇİGİL (4) , Mine AFACAN FINDIKLI (5) Öz: 2015 yılında gerçekleştirilen Birleşmiş Milletler (BM) Sürdürülebilir Kalkınma Konferansında "Gündem 2030: BM Sürdürülebilir Kalkınma Amaçları" kabul edilmiştir. Üniversiteler, bu amaçların hayata geçirilmesi sürecinde yol gösterici olarak görülmüş; hem yeni fikirlerin yayılması ve benimsetilmesi kabiliyetleri hem de eğitim ve araştırma olanaklarıyla kilit bir rol üstelenmişl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
1
0
2
Order By: Relevance
“…This is consistent with previous studies, and the study concluded that the top 20 universities were also leaders in achieving sustainability [72]. Gedikkaya et al [73] concluded, in their study, that universities in Türkiye had an increasing awareness and interest in sustainable development, and every year, more universities were included in indexes, such as STARS, UI, GreenMetric, and Times Higher Education Impact Rankings. However, our study showed that not all Turkish universities tend to include all SDGs in their strategies.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with previous studies, and the study concluded that the top 20 universities were also leaders in achieving sustainability [72]. Gedikkaya et al [73] concluded, in their study, that universities in Türkiye had an increasing awareness and interest in sustainable development, and every year, more universities were included in indexes, such as STARS, UI, GreenMetric, and Times Higher Education Impact Rankings. However, our study showed that not all Turkish universities tend to include all SDGs in their strategies.…”
Section: Discussionsupporting
confidence: 89%
“…Only seven universities among all published sustainability reports; the researchers [13] associate this situation with the lack of a standard sustainability report template by the Higher Education Council. [14] investigated the interest of Turkish universities in sustainability indexes such as GreenMetric. In 2010 only one Turkish university was included in the UI GreenMetric World University Rankings; in 2014, 10 universities were in the ranking.…”
Section: Universities and Sustainability Activities In Türkiyementioning
confidence: 99%
“…Bu derecelendirme listeleri üniversitelerin görünürlüğünü arttırmakta, ilaveten birçok üniversite için farkındalık ve motivasyon oluşturmaktadır. Bu çalışmada, SKA önceleyen STARS, GreenMetric ve THE Times Yükseköğrenim Etki Sıralaması LEEDS ve BREAMS indeksleri ve kriterleri verilmiştir [1].…”
Section: Avrupa Birliği Birleşmiş Milletlerunclassified
“…Bu çalışmalar ülkeler düzeyinde özellikle de Avrupa Birliği (AB) ve Birleşmiş Milletler (BM) çerçevesinde konferanslarla ortaya konmuştur. Bu çalışmalar özet olarak Tablo 1'de verilmiştir [1].…”
unclassified